KEPUASAN PASIEN TERHADAP PELAYANAN INTRANATAL CARE DI PUSKESMAS SIATAS BARITA TAPANULI UTARA TAHUN 2021 - Nurhamida Fitri (Excellent Midwifery Journal, 2021)
Patient satisfaction is one of the most important things in reviewing the quality of health services, especially Intranatal care services in a Puskesmas, this condition is evident from the data presented, namely the number of complaints from patients and the public about the quality of health services, if the quality of health services is not always maintained and increased the possibility of the number of patients will shrink. This study aims to identify patient satisfaction with Intranatal Care services at Siatas Barita Health Center which is assessed from 5 aspects, namely tangible, reliability, responsiveness, assurance and empathy. The design used in this study is descriptive design, namely to identify patient satisfaction with intranatal care services at Siatas Barita Health Center with a total sample of 47 people, sampling through convenience sampling technique using a questionnaire as a research instrument. The results showed (0%) expressed very satisfied, 45 patients (95%) expressed satisfaction and two patients (5%) expressed dissatisfaction with the intranatal care services provided by health workers at the Siatas Barita Health Center. Based on the research it can be concluded that the majority of patients expressed satisfaction with intranatal care services at the Siatas Barita Health Center, and only two patients (5%) expressed dissatisfaction, especially with the services in welcoming patients who came to visit and the hospitality of health workers, therefore officers must further improve their abilities and care for the complaints felt by patients in order to realize the patient's satisfaction with the services provided by health workers, especially in intranatal care services at Siatas Barita Tapanuli Utara Health Center. Keywords:  Patient Satisfaction, Intranatal Care Services